Effect of Postoperative Adverse Events on Hospitalization Expenditures and Length of Stay Among Surgery Patients in Taiwan: A Nationwide Population-Based Case-Control Study - Yang, Chih-Chieh; Chuang, Yi-Fei; Chen, Pei-En; Tao, Ping; Tung, Tao-Hsin; Chien, Ching-Wen (Frontiers in Medicine, 2021)
Background. The current study sought to determine the incidence of postoperative adverse events (AEs) based on data from the 2006 Taiwan National Health Insurance Research Database (NHIRD). Methods. This retrospective case-control study included patients who experienced postoperative AEs in 387 hospitals throughout Taiwan in 2006. The independent variable was the presence or absence of ten possible postoperative AEs, as identified by patient safety indicators (PSIs). Results. A total of 17,517 postoperative AEs were identified during the study year. PSI incidence ranged from 0.1/1,000 admissions (obstetric trauma-cesarean section) to 132.6/1,000 admissions (obstetric trauma with instrument). Length of stay (LOS) associated with postoperative AEs ranged from 0.10 days (obstetric trauma with instrument) to 14.06 days (postoperative respiratory failure). Total hospitalization expenditures (THEs) ranged from 363.7 New Taiwan Dollars (obstetric trauma without instrument) to 263,732 NTD (postoperative respiratory failure). Compared to patients without AEs, we determined that the THEs were 2.13 times in cases of postoperative AE and LOS was 1.72 times higher. Conclusions. AEs that occur during hospitalization have a major impact on THEs and LOS.